Curing time dependent properties of cement treated Bangkok clay - Soe Moe Kyaw Win; Noppadol Phien-Wej; Bergado, Dennes T.; Kohgo, Yuji; Asian Institute of Technology Partial Scholarship (Bangkok : Asian Institute of Technology, 1997)
The strength and deformation characteristics and the time dependent behaviour of the cement treated Bangkok clay were studied through comprehensive series of unconfined compression and oedometer tests. The base clay used were lightly overconsolidated soft Bangkok clay, at a depth of 3 to 4 m from AIT campus. Type I Portland cement powder was used to stabilize the soft clay and cement content of 150 and 200 kg/m3 were used. Both dry and slurry mixing were used for Unconfined Compression Test and Oedometer Tests. For Unconfined Compression Tests, curing period of 3, 7, 14, 28, 60, 90 and 120 days, w/c ratio of 0.5, 0.6, 0.8, 1.0, 1.2 were used. For oedometer tests, curing period of 7, 28, 60 and 90 days with w/c ratio of 1.0 were used. The unconfined compressive strength of cement treated sam~les were found to increase with curing time. For dry mixing, cement content of 150 kg/m could be regarded as an optimum cement content for long term curing period. Strength increment of sluny mixed samples reduce with increase in w/c ratio. Oedometer tests revealed that the cement treatment caused substantial improvement of consolidation properties, apparent preconsolidation pressure, reduction of compression index (Cc), increase the value of coefficient of consolidation (Cv)·. Coefficient of permeability of cement treated soil is smaller than the untreated soil, and hence it is not suitable as material for vertical drain. As compared with previous research from AIT, laborato1y studies on the use of various additive to soft Bangkok clay indicated that cement is the most superior additive in achieving higher strength within the optimum specific time of curing.The improved strength of treated samples are dependent on strength and physical prope1ties of untreated clay, mixing method, sample preparation, sample curing method, curing time, w/c ratio and cement content. Unconfined compressive strength of treated samples from the same location can differ a lot depending on sample preparation and curing method
A thesis submitted in partial fulfillment of the requirements for the degree of Master of Science, School of Civil Engineering
Thesis (M. Sc.) - Asian Institute of Technology, 1997
Keywords: Soil stabilization -- Thailand -- Bangkok